2019
DOI: 10.4048/jbc.2019.22.e20
|View full text |Cite
|
Sign up to set email alerts
|

High Survivin and Low Zinc Finger of the Cerebellum 1 Expression Indicates Poor Prognosis in Triple-negative Breast Carcinoma

Abstract: Purpose Triple-negative breast carcinoma (TNBC) is accompanied with high risk of metastasis and recurrence. The present study aimed to explore the clinicopathological and prognostic roles of putative tumor-related genes in patients with TNBC. Methods Thirty pairs of frozen-thawed tumors were used to select reliable indicators via real-time quantitative polymerase chain reaction (RT-qPCR). Then, 150 pathology specimens were used to evaluate the expression of proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, the expression of survivin appeared to be of higher importance for the malignant progression of TNBC instead of non-TNBC, where patients with TNBC showing higher expression levels of survivin tended to exhibit more severe malignancy, resulting in poorer prognoses. Shi et al also drew a similar conclusion in a previous study with TNBC, whereby survivin-positive patients tended to have shorter OS and disease-free survival times (36), but Dogu et al and Jha et al did not observe any effects exerted by survivin on the prognosis of patients with TNBC (45,46). These discrepancies may be attributed to the different antibodies used, distinct sample groups or the cut-off criteria set prior to evaluation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, the expression of survivin appeared to be of higher importance for the malignant progression of TNBC instead of non-TNBC, where patients with TNBC showing higher expression levels of survivin tended to exhibit more severe malignancy, resulting in poorer prognoses. Shi et al also drew a similar conclusion in a previous study with TNBC, whereby survivin-positive patients tended to have shorter OS and disease-free survival times (36), but Dogu et al and Jha et al did not observe any effects exerted by survivin on the prognosis of patients with TNBC (45,46). These discrepancies may be attributed to the different antibodies used, distinct sample groups or the cut-off criteria set prior to evaluation.…”
Section: Discussionmentioning
confidence: 69%
“…In terms of TNBC, Yamanaka et al found that inhibition of survivin expression can significantly suppress the metastasis of TNBC MDA-MB-231 cells, while also significantly prolonging the survival time of tumor-bearing mice (35). Furthermore, Shi et al (36) found that survivin expression was associated with the histological grade and TNM stage of patients with TNBC, where the survival rate of patients with survivin-positive TNBC was lower. Observations from these aforementioned studies suggest that survivin may be involved in the pathophysiological process of TNBC and therefore attention should be paid to the potential value of applying survivin as a prognostic indicator.…”
Section: Significance Of Combined Tgf-β1 and Survivin Expression On T...mentioning
confidence: 99%
“…According to the authors, survivin and epidermal growth factor receptor expression evaluated by immunohistochemistry were considered of prognostic value for TNBC. Likewise, survivin expression together with zinc finger of the cerebellum 1 also showed prognostic potential 13 ; in this case, the expression of these was evaluated in frozen tumor samples using quantitative polymerase chain reaction (qPCR) and in paraffin-embedded samples by immunohistochemistry. Our results show that the isolated expression of survivin obtained by qPCR can be considered a prognostic marker for all breast tumor subtypes, and that this evaluation can be performed on stored paraffin-embedded samples.…”
Section: Discussionmentioning
confidence: 99%
“…Specific inhibition of survivin could induce apoptosis and suppress the proliferation of hepatocellular carcinoma (HCC), and similar effects were observed in CRC, leukemia, and breast cancer, among others. Therefore, survivin might be a promising target for tumor inhibition ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%